A water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitrification catalyst and its preparation method

By developing an ultra-low temperature denitrification catalyst composed of ZSM-5 molecular sieve, titanium dioxide, diatomaceous earth and silane coupling agent KH550, which is water-resistant, sulfur-resistant and poison-resistant, the denitrification efficiency of the existing technology under low-temperature flue gas conditions has been solved. It reduces the problem of poisoning and achieves high-efficiency denitrification and improved anti-poisoning performance in the range of 100℃~150℃.

CN118988392BActive Publication Date: 2025-01-24SHANGHAI HANYU ENVIRONMENTAL PROTECTION MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411479093.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

In the existing SCR technology, V2O5/TiO2 catalysts can only be used in flue gases between 300℃ and 420℃. When they are below 300℃, sulfur oxidation and water poisoning are prone to occur. The poisoning is irreversible and it is difficult to adapt to low-temperature flue gases. condition.

Method used

Develop an ultra-low temperature denitration catalyst that is resistant to water, sulfur, and poisoning. ZSM-5 molecular sieve, titanium dioxide, diatomaceous earth, silane coupling agent KH550 and other materials are mixed in specific proportions, and subjected to processes such as high-pressure extrusion and hot air drying. Processed to form a highly active catalyst.

Benefits of technology

This catalyst shows high catalytic efficiency, strong anti -poisoning ability, and good abrasion resistance within the range of 100 ° C ~ 150 ° C. It is suitable for use at low temperature flue gas conditions, especially at 100 ° C to 150 ° C. It is better than existing technology than existing technology. Performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to a water-resistant, sulfur-resistant, and poison-resistant ultra-low temperature denitration catalyst and a preparation method thereof, and belongs to the technical field of flue gas denitration catalysts. The mixture of copper nitrate, nickel nitrate, and chromium nitrate in the catalyst synergizes with rubidium nitrate, and after mixing, extrusion, and roasting, a highly active catalytic center is formed, which can effectively promote NO at low temperatures. x The reduction reaction improves the low-temperature activity of the catalyst; the ZSM‑5 molecular sieve and titanium dioxide in the catalyst carrier have excellent selectivity and hydrophobicity, which can effectively prevent SO2, SO3, water molecules, etc. from occupying and destroying the active sites of the catalyst. The addition of silane coupling agent KH550 further enhances the sulfur and water resistance of the carrier, so that the catalyst can still maintain a high catalytic activity in a sulfur-containing and water-containing flue gas environment; the auxiliary agent ammonium heptamolybdate in the catalyst helps to improve the catalyst's anti-poisoning ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flue gas denitration catalysts and relates to a water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitration catalyst and a preparation method thereof. Background Art

[0002] Among the many pollutants, nitrogen oxides (NO x ) emissions are particularly prominent, which mainly come from combustion activities in the process of industrial production and energy consumption. Therefore, the importance of research and development and application of flue gas denitrification technology is becoming increasingly prominent.

[0003] Currently, the removal of NO x The main methods used are selective non-catalytic reduction (SNCR), selective catalytic reduction (SCR) and a combination of SNCR and SCR. Among them, SNCR is highly dependent on temperature and has a relatively low denitrification rate (only 40% to 60%), while selective catalytic reduction technology (SCR) has been widely used in many countries with strict flue gas emission standards and can meet higher emission standards. Therefore, SCR is recognized as the most effective and mature process. In recent years, SCR technology has become a popular technology for controlling NO in actual flue gas treatment due to its high denitrification performance and relatively mature process. x One of the most effective techniques for reducing emissions. Therefore, as the core of SCR technology, the reasonable design and use of denitrification catalysts can effectively improve denitrification efficiency, enhance stability and reduce production costs. However, the V2O5 / TiO2 catalysts currently used in SCR can usually only be used in flue gas at 300℃~420℃. If denitrification is carried out in flue gas conditions below 300℃, serious sulfur oxide poisoning and water poisoning, as well as alkali (alkaline earth) metal poisoning, will occur, and this poisoning is irreversible. However, in non-electric industries, such as steel, cement, garbage incineration, biomass incineration, hazardous waste incineration, catalytic cracking, glass, ceramics and other production processes, the flue gas temperature is generally lower than 300℃, or even lower than 150℃. The cement industry made from carbide slag has the characteristics of high nitrogen oxide emission concentration, large fluctuations, large amounts of ammonia generated during the drying process of raw materials, and high alkalinity of dust. In order to meet the standards for nitrogen oxide emissions and ammonia emissions at the same time, low-temperature or ultra-low-temperature SCR denitrification can only be carried out after the tail bag filter.

[0004] The wide variety of furnaces and kilns in these industries, as well as the complex and varied production processes, result in different flue gas compositions and temperatures. For example, the flue gas temperatures emitted by sintering machines, pelletizing furnaces, and coke ovens in the steel industry are usually low, which poses a challenge to traditional selective catalytic reduction (SCR) denitrification technology. Traditional SCR technology requires a high operating temperature for the catalyst, and in these low temperature environments, there is no suitable heat source available, and if external heating is used, the operating cost will increase significantly. The current common method is to heat the flue gas to 300°C or above so that medium and high temperature catalysts can be used for denitrification.

[0005] Therefore, for these specific industries, it is necessary to develop new denitrification technologies that are suitable for low-temperature flue gas and improve existing catalysts to improve efficiency and adaptability at low temperatures. Summary of the invention

[0006] The purpose of the present invention is to provide a water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitrification catalyst mainly suitable for the range of 100°C to 150°C and a preparation method thereof, which has the characteristics of high catalytic efficiency.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitration catalyst, which is composed of 5-15% active component, 75-85% carrier, and 5-15% auxiliary agent by mass percentage.

[0009] Wherein, the preparation method of the carrier is as follows:

[0010] S11: ZSM-5 molecular sieve and titanium dioxide were mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture A;

[0011] S12: Grind the diatomite in a ball mill at a speed of 500 r / min for 0.5 h, disperse it in a 10% by mass nitric acid solution, heat it to 60° C., ultrasonicate it for 1 h, cool it to room temperature, wash it with deionized water, and dry it at 80° C. for 12 h to obtain diatomite powder B;

[0012] S13: Mix the mixture A and the diatomaceous earth powder B in a mass ratio of 1:(1-3), and grind them in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture C;

[0013] S14: adding silane coupling agent KH550 to deionized water to prepare a solution with a mass fraction of 30-50%, heating to 60° C. to obtain solution D;

[0014] S15: putting the mixture C into the solution D, wherein the mass ratio of the mixture C to the silane coupling agent KH550 is 2:1, stirring at 60° C. at a speed of 150 r / min for 4 h, filtering, and drying at 80° C. for 12 h to obtain the carrier;

[0015] Furthermore, the preparation method of the active component is as follows:

[0016] S21: copper nitrate, nickel nitrate and chromium nitrate were mixed in a mass ratio of 2:1:1, 1 wt % of polyethylene glycol 2000 was added, and the mixture was ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture E;

[0017] S22: Rubidium nitrate is dissolved in deionized water to prepare a rubidium nitrate solution with a mass fraction of 30-40%, and mixture E is dispersed in the rubidium nitrate solution, wherein the mass ratio of mixture E to rubidium nitrate is 2:1, the temperature is raised to 50°C, and stirred at a speed of 200r / min for 1h, 1wt% glycine is added to the mixed solution, and after continuing to stir for 0.5h, it is transferred to a muffle furnace preheated to 250-300°C and burned for 2-3min, and then heated to 500°C and roasted for 4h, the heating rate of the muffle furnace is 5°C / min, and after the roasting is completed, it is cooled and ground to obtain the active component, and the particle size of the active component obtained by grinding is 800 mesh.

[0018] Further, the preparation method of the auxiliary agent is as follows:

[0019] S31: dissolving a cationic surfactant in deionized water to obtain a solution with a mass fraction of 50%, and heating the solution to 60° C. to obtain a solution F;

[0020] S32: Add ammonium heptamolybdate to solution F, wherein the mass ratio of ammonium heptamolybdate to the cationic surfactant is 2:3, perform ultrasonic treatment at 60°C for 0.5h, filter after the completion of ultrasonic treatment, dry at 80°C for 12h, cool and grind after drying to obtain the auxiliary agent.

[0021] Furthermore, the cationic surfactant in S31 is one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and hexadecyltrimethylammonium bromide.

[0022] Furthermore, the particle size of the additive obtained by grinding in S32 is 800 mesh.

[0023] A method for preparing a water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitrification catalyst. The specific process of the catalyst preparation method is as follows:

[0024] S61: Put the active component, carrier and auxiliary agent into a high-speed mixer according to the proportion, add 1wt% oxalic acid, add a certain amount of deionized water, mix and stir, the mixer speed is 3000r / min, the time is 5h, and a muddy mixture G is obtained;

[0025] S62: The muddy mixture G is extruded into a through-hole square honeycomb body by a high-pressure extruder through an integrated die, and cut into a required length; then dried by hot air, kept at 10 temperature sections between 25 and 60°C for 18 to 24 hours, and then calcined at 120 to 560°C for 31 to 42 hours. Thus, an ultra-low temperature denitration catalyst of a square honeycomb body is obtained.

[0026] Furthermore, the mixture G in S61 is a long strip of mud.

[0027] Furthermore, in S62, hot air is used for drying, and the temperature is controlled by a computer program and kept warm for 18 to 24 hours at each of 25°C, 28°C, 31°C, 35°C, 40°C, 45°C, 50°C, 55°C, 58°C, and 60°C, respectively, wherein the humidity in the drying room is required to be maintained at more than 80% before 40°C; and then the baking is carried out by a program-controlled electric heating segmented insulation method, with the residence time in the low temperature zone of 120 to 180°C and the medium temperature zone of 300 to 400°C being not less than 3 hours and 13 hours, respectively, and the temperature in the high temperature zone is controlled within the range of 480 to 560°C according to performance requirements, with the residence time being not less than 15 hours, and the total residence time being 31 to 42 hours.

[0028] Furthermore, the catalyst prepared in S62 is a cube honeycomb catalyst.

[0029] The catalyst prepared by the present invention has good activity at low or ultra-low temperatures, high denitration efficiency, strong anti-poisoning ability, high strength, and good wear resistance, and is suitable for use at a flue gas temperature of 100 to 280° C., especially in the range of 100 to 150° C. It has more superior performance than the prior art.

[0030] The active component is the core of the catalytic reaction and determines the basic catalytic performance of the catalyst. The present invention forms an efficient catalytic site through the synergistic effect of the mixture of copper nitrate, nickel nitrate and chromium nitrate and rubidium nitrate, which promotes the reaction of NO xreduction reaction; the carrier provides the skeleton structure of the catalyst, increases the specific surface area and porosity, and is beneficial to the dispersion of active components and the diffusion of gas molecules. The combination of ZSM-5 molecular sieve, titanium dioxide and diatomaceous earth further enhances the stability and sulfur and water resistance of the carrier; the addition of additives can improve the catalyst's resistance to alkali metal and alkaline earth metal poisoning and stability by adjusting the surface properties of the catalyst. Ammonium heptamolybdate, as an electronic additive, promotes the redox cycle of the active components; the addition of cationic surfactants improves the surface charge distribution of the carrier and enhances the interaction with the active components.

[0031] The invention forms a highly active catalytic site through the synergistic effect of the mixture of copper nitrate, nickel nitrate and chromium nitrate and rubidium nitrate. During the roasting process, the nitrate will decompose to form corresponding metal oxides, and these oxides are the main active sites of the catalytic reaction. The addition of glycine promotes the uniform dispersion of the nitrate and the stability of the metal ions, thereby improving the catalytic activity at low temperature.

[0032] Copper oxide is one of the main active components in the catalyst. x The copper oxide has a significant catalytic effect on the reduction reaction. Copper oxide shows high catalytic activity at low temperature and can accelerate the reaction of NH3 and NO x The copper oxide provides abundant active sites for the redox reaction between NH3 and NO. x molecules, reducing the activation energy of the reaction and promoting the conversion of reactants; nickel oxide plays an auxiliary catalytic role in the catalyst and enhances the overall activity of the catalyst. The addition of nickel can improve the pore structure of the catalyst, improve the mass transfer efficiency, and enhance the anti-poisoning performance of the catalyst. Nickel oxide and copper oxide optimize the charge distribution and redox state of the catalyst surface through electron transfer and interaction, thereby improving the efficiency of the catalytic reaction; chromium oxide plays a role in stabilizing the structure in the catalyst and improving the thermal stability and mechanical strength of the catalyst. At the same time, the addition of chromium may also improve the water resistance of the catalyst. Chromium oxide forms a stable composite structure with copper and nickel oxides, enhancing the catalyst's ability to resist high temperatures and water vapor erosion; rubidium is added to the active component as an additive. The addition of rubidium can enhance the anti-poisoning performance of the catalyst and can also optimize NH3 and NO by adjusting the charge distribution and acid-base properties of the catalyst surface. x During the adsorption and activation process on the catalyst surface, rubidium can also enhance the catalyst's resistance to poisoning substances such as sulfur oxides.

[0033] ZSM-5 molecular sieve has a specific pore structure and acidic sites, which can adsorb and activate NH3 and NO x, promoting the redox reaction between them. The treated diatomite powder has a good pore structure and a large specific surface area, and can be used as a carrier of the catalyst to improve the structural stability of the catalyst and prevent the catalyst from sintering or agglomerating at high temperature and during the reaction. During the preparation process, ZSM-5 molecular sieve and titanium dioxide can be evenly dispersed in the pores of the diatomite powder to form a stable composite structure. Adding it to the catalyst as a carrier can further enhance the mechanical strength and thermal stability of the catalyst, and the carrier is further modified using the silane coupling agent KH550, which increases the wettability and dispersibility of the carrier, so that it can be better combined with other components of the catalyst and improve the overall performance of the catalyst.

[0034] The complex of cationic surfactant and ammonium heptamolybdate is added to the catalyst as an additive, which can improve the hydrophobicity of the catalyst surface and reduce the adsorption of water molecules on the catalyst surface, thereby enhancing the water resistance of the catalyst. The reduction of water molecules can reduce its NO x Competition with NH3 for adsorption on the catalyst surface maintains a high catalytic activity; ammonium heptamolybdate has redox ability and can be added to the catalyst as an auxiliary agent to react with sulfur oxides, alkali metals, alkaline earth metals or other poisoning substances on the catalyst surface, thereby reducing the occupation of these substances on the active sites of the catalyst and improving the anti-poisoning ability of the catalyst; there is also a synergistic effect between the auxiliary agent and the catalyst carrier in the present invention, and the auxiliary agent can further optimize the performance of the catalyst by changing the physical and chemical properties of the carrier surface (such as pore structure, specific surface area, surface acidity and alkalinity, etc.), and the interaction between the two can also promote the transfer of electrons and the progress of the catalytic reaction.

[0035] The catalyst prepared by the present invention has the characteristics of low temperature, high activity, strong sulfur resistance, water resistance, strong anti-poisoning ability and high catalytic efficiency. This is because the active components in the catalyst undergo combustion and roasting processes in a muffle furnace to form highly active catalytic centers. These catalytic centers can effectively promote NO at low temperatures and x reduction reaction, thereby improving the low temperature and activity of the catalyst.

[0036] The ZSM-5 molecular sieve and titanium dioxide in the catalyst carrier have excellent hydrophobic properties, which can effectively prevent moisture from occupying and destroying the active sites of the catalyst. At the same time, the addition of silane coupling agent KH550 further enhances the water resistance of the carrier, allowing the catalyst to maintain a high catalytic activity in a water-containing flue gas environment.

[0037] The additive ammonium heptamolybdate in the catalyst helps improve the anti-poisoning ability of the catalyst. The additive can adsorb and neutralize harmful substances (such as SO2) in the flue gas to prevent them from poisoning the active sites of the catalyst, further enhancing its anti-poisoning performance.

[0038] The active components, carriers and additives of the catalyst form a good synergistic effect, which enables the catalyst to achieve efficient NO removal at low temperature and x At the same time, the particle size of the catalyst has been optimized to increase the contact area between the catalyst and the flue gas and the reaction rate, thereby improving the catalytic efficiency.

[0039] Beneficial effects of the present invention:

[0040] (1) The present invention forms highly active catalytic sites through the synergistic effect of the mixture of copper nitrate, nickel nitrate and chromium nitrate and rubidium nitrate. During the calcination process, the nitrate will decompose to form corresponding metal oxides, which are the main active sites of the catalytic reaction. The addition of glycine promotes the uniform dispersion of nitrate and the stability of metal ions, thereby improving the catalytic activity at low temperatures and temperatures. The combination of these oxides can form a complementary effect, thereby improving the overall catalytic activity of the catalyst at low temperatures and temperatures;

[0041] (2) The catalyst carrier is prepared by combining ZSM-5 molecular sieve, titanium dioxide and modified diatomaceous earth, which provides a rich pore structure and a large specific surface area, which is conducive to the diffusion and adsorption of gas molecules, further enhancing the catalytic efficiency at low temperatures and temperatures;

[0042] (3) The complex of cationic surfactant and ammonium heptamolybdate is added to the catalyst as an auxiliary agent. The cationic surfactant reduces the adsorption of water molecules by changing the hydrophilicity and hydrophobicity of the catalyst surface; while ammonium heptamolybdate reacts with poisoning substances through its redox ability to restore the activity of the catalyst. The two work together to significantly improve the catalyst's water resistance and anti-poisoning ability. DETAILED DESCRIPTION

[0043] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0044] Example 1

[0045] The catalyst is composed of 10% active component, 80% carrier and 10% auxiliary agent by mass percentage.

[0046] The preparation method of the carrier is as follows:

[0047] S11: ZSM-5 molecular sieve and titanium dioxide were mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture A; S12: Diatomaceous earth was ground in a ball mill at a speed of 500 r / min for 0.5 h, and then dispersed in a nitric acid solution with a mass fraction of 10%, heated to 60°C, ultrasonicated for 1 h, cooled to room temperature, washed with deionized water, and dried at 80°C for 12 h to obtain diatomaceous earth powder B;

[0048] S13: Mix the mixture A and the diatomaceous earth powder B in a mass ratio of 1:2, and grind them in a ball mill at a rotation speed of 500 r / min for 0.5 h to obtain a mixture C;

[0049] S14: adding silane coupling agent KH550 to deionized water to prepare a solution with a mass fraction of 40%, heating to 60° C. to obtain solution D;

[0050] S15: putting the mixture C into the solution D, wherein the mass ratio of the mixture C to the silane coupling agent KH550 is 2:1, stirring at 60° C. at a speed of 150 r / min for 4 h, filtering, and drying at 80° C. for 12 h to obtain the carrier;

[0051] The preparation method of the active component is as follows:

[0052] S21: copper nitrate, nickel nitrate and chromium nitrate were mixed in a mass ratio of 2:1:1, 1 wt % of polyethylene glycol 2000 was added, and the mixture was ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture E;

[0053] S22: dissolving rubidium nitrate in deionized water to prepare a rubidium nitrate solution with a mass fraction of 40%, dispersing mixture E in the rubidium nitrate solution, wherein the mass ratio of mixture E to rubidium nitrate is 2:1, heating to 50°C, and stirring at a speed of 200r / min for 1h, adding 1wt% glycine to the mixed solution, continuing to stir for 0.5h, transferring to a muffle furnace preheated to 300°C and burning for 2min, then heating to 500°C and calcining for 4h at a heating rate of 5°C / min, and after calcination, cooling and grinding to obtain the active component, wherein the particle size of the ground active component is 800 mesh;

[0054] The preparation method of the auxiliary agent is as follows:

[0055] S31: dissolving sodium dodecyl sulfate in deionized water to obtain a solution with a mass fraction of 50%, and heating the solution to 60° C. to obtain a solution F;

[0056] S32: Add ammonium heptamolybdate to solution F, wherein the mass ratio of ammonium heptamolybdate to the cationic surfactant is 2:3, and ultrasonicate is performed at 60°C for 0.5h. After the ultrasonication is completed, the solution is filtered, dried at 80°C for 12h, cooled and ground after drying to obtain the auxiliary agent, wherein the particle size of the auxiliary agent obtained by grinding is 800 mesh.

[0057] A method for preparing a water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitrification catalyst. The specific process of the catalyst preparation method is as follows:

[0058] S61: Put the active component, carrier and auxiliary agent into a high-speed mixer according to the proportion, add 1wt% oxalic acid, add a certain amount of deionized water, mix and stir, the mixer speed is 3000r / min, the time is 5h, and a muddy mixture G is obtained;

[0059] S62: The muddy mixture G is extruded into a through-hole square honeycomb body by a high-pressure extruder using an integrated die, and cut into the required length; then dried by hot air, and the temperature is controlled by a computer program and kept warm for 20 hours at 25°C, 28°C, 31°C, 35°C, 40°C, 45°C, 50°C, 55°C, 58°C, and 60°C, respectively, and the humidity in the drying room is required to be maintained above 80% before 40°C; then calcined by program-controlled electric heating in a segmented insulation manner, with the residence time in the low temperature zone of 150°C and the medium temperature zone of 350°C being 3 hours and 13 hours respectively, and the temperature in the high temperature zone is controlled at 520°C according to the performance requirements, the residence time is 15 hours, and the total residence time is 31 hours, to obtain the catalyst.

[0060] Example 2

[0061] The catalyst is composed of 15% active component, 75% carrier and 10% auxiliary agent by mass percentage.

[0062] The preparation method of the carrier is as follows:

[0063] S11: ZSM-5 molecular sieve and titanium dioxide were mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture A; S12: Diatomaceous earth was ground in a ball mill at a speed of 500 r / min for 0.5 h, and then dispersed in a nitric acid solution with a mass fraction of 10%, heated to 60°C, ultrasonicated for 1 h, cooled to room temperature, washed with deionized water, and dried at 80°C for 12 h to obtain diatomaceous earth powder B;

[0064] S13: Mix the mixture A and the diatomaceous earth powder B in a mass ratio of 1:1, and grind them in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture C;

[0065] S14: adding silane coupling agent KH550 to deionized water to prepare a solution with a mass fraction of 30%, heating to 60° C. to obtain solution D;

[0066] S15: putting the mixture C into the solution D, wherein the mass ratio of the mixture C to the silane coupling agent KH550 is 2:1, stirring at 60° C. at a speed of 150 r / min for 4 h, filtering, and drying at 80° C. for 12 h to obtain the carrier;

[0067] The preparation method of the active component is as follows:

[0068] S21: copper nitrate, nickel nitrate and chromium nitrate were mixed in a mass ratio of 2:1:1, 1 wt % of polyethylene glycol 2000 was added, and the mixture was ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture E;

[0069] S22: dissolving rubidium nitrate in deionized water to prepare a rubidium nitrate solution with a mass fraction of 30%, dispersing mixture E in the rubidium nitrate solution, wherein the mass ratio of mixture E to rubidium nitrate is 2:1, heating to 50°C, and stirring at a speed of 200r / min for 1h, adding 1wt% glycine to the mixed solution, continuing to stir for 0.5h, transferring to a muffle furnace preheated to 250°C and burning for 3min, then heating to 500°C and roasting for 4h, with a heating rate of 5°C / min, and after roasting, cooling and grinding to obtain the active component, the particle size of the ground active component is 800 mesh;

[0070] The preparation method of the auxiliary agent is as follows:

[0071] S31: dissolving sodium dodecyl sulfate in deionized water to obtain a solution with a mass fraction of 50%, and heating the solution to 60° C. to obtain a solution F;

[0072] S32: Add ammonium heptamolybdate to solution F, wherein the mass ratio of ammonium heptamolybdate to the cationic surfactant is 2:3, and ultrasonicate is performed at 60°C for 0.5h. After the ultrasonication is completed, the solution is filtered, dried at 80°C for 12h, cooled and ground after drying to obtain the auxiliary agent, wherein the particle size of the auxiliary agent obtained by grinding is 800 mesh.

[0073] A method for preparing a water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitrification catalyst. The specific process of the catalyst preparation method is as follows:

[0074] S61: Put the active component, carrier and auxiliary agent into a high-speed mixer according to the proportion, add 1wt% oxalic acid, add a certain amount of deionized water, mix and stir, the mixer speed is 3000r / min, the time is 5h, and a muddy mixture G is obtained;

[0075] S62: The muddy mixture G is extruded into a through-hole square honeycomb body by a high-pressure extruder using an integrated die, and cut into the required length; then dried by hot air, and the temperature is controlled by a computer program and kept in sections at 25°C, 28°C, 31°C, 35°C, 40°C, 45°C, 50°C, 55°C, 58°C, and 60°C for 18 h at each of the above temperatures, wherein the humidity in the drying room is required to be maintained at more than 80% before 40°C; then calcined by program-controlled electric heating in a sectioned insulation manner, with the residence time in the low temperature zone of 120°C and the medium temperature zone of 300°C being 4 h and 13 h respectively, and the temperature in the high temperature zone is controlled at 480°C according to the performance requirements, with a residence time of 18 h and a total residence time of 35 h, to obtain the catalyst.

[0076] Example 3

[0077] The catalyst is composed of 5% active component, 85% carrier and 10% auxiliary agent by mass percentage.

[0078] The preparation method of the carrier is as follows:

[0079] S11: ZSM-5 molecular sieve and titanium dioxide were mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture A; S12: Diatomaceous earth was ground in a ball mill at a speed of 500 r / min for 0.5 h, and then dispersed in a nitric acid solution with a mass fraction of 10%, heated to 60°C, ultrasonicated for 1 h, cooled to room temperature, washed with deionized water, and dried at 80°C for 12 h to obtain diatomaceous earth powder B;

[0080] S13: Mix the mixture A and the diatomaceous earth powder B in a mass ratio of 1:3, and grind them in a ball mill at a rotation speed of 500 r / min for 0.5 h to obtain a mixture C;

[0081] S14: adding silane coupling agent KH550 to deionized water to prepare a solution with a mass fraction of 50%, heating to 60° C. to obtain solution D;

[0082] S15: putting the mixture C into the solution D, wherein the mass ratio of the mixture C to the silane coupling agent KH550 is 2:1, stirring at 60° C. at a speed of 150 r / min for 4 h, filtering, and drying at 80° C. for 12 h to obtain the carrier;

[0083] The preparation method of the active component is as follows:

[0084] S21: copper nitrate, nickel nitrate and chromium nitrate were mixed in a mass ratio of 2:1:1, 1 wt % of polyethylene glycol 2000 was added, and the mixture was ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture E;

[0085] S22: dissolving rubidium nitrate in deionized water to prepare a rubidium nitrate solution with a mass fraction of 40%, dispersing mixture E in the rubidium nitrate solution, wherein the mass ratio of mixture E to rubidium nitrate is 2:1, heating to 50°C, and stirring at a speed of 200r / min for 1h, adding 1wt% glycine to the mixed solution, continuing to stir for 0.5h, transferring to a muffle furnace preheated to 300°C and burning for 2min, then heating to 500°C and calcining for 4h at a heating rate of 5°C / min, and after calcination, cooling and grinding to obtain the active component, wherein the particle size of the ground active component is 800 mesh;

[0086] The preparation method of the auxiliary agent is as follows:

[0087] S31: dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a solution with a mass fraction of 50%, and heating the solution to 60° C. to obtain a solution F;

[0088] S32: Add ammonium heptamolybdate to solution F, wherein the mass ratio of ammonium heptamolybdate to the cationic surfactant is 2:3, and ultrasonicate is performed at 60°C for 0.5h. After the ultrasonication is completed, the solution is filtered, dried at 80°C for 12h, cooled and ground after drying to obtain the auxiliary agent, wherein the particle size of the auxiliary agent obtained by grinding is 800 mesh.

[0089] A method for preparing a water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitrification catalyst. The specific process of the catalyst preparation method is as follows:

[0090] S61: Put the active component, carrier and auxiliary agent into a high-speed mixer according to the proportion, add 1wt% oxalic acid, add a certain amount of deionized water, mix and stir, the mixer speed is 3000r / min, the time is 5h, and a muddy mixture G is obtained;

[0091] S62: The muddy mixture G is extruded into a through-hole square honeycomb body by a high-pressure extruder using an integrated die, and cut into the required length; then dried by hot air, and the temperature is controlled by a computer program and kept in sections at 25°C, 28°C, 31°C, 35°C, 40°C, 45°C, 50°C, 55°C, 58°C, and 60°C for 24 h at each of the above temperatures, wherein the humidity in the drying room is required to be maintained at more than 80% before 40°C; then calcined by program-controlled electric heating in a sectioned insulation manner, with the residence time in the low temperature zone of 180°C and the medium temperature zone of 400°C being 6 h and 16 h respectively, and the temperature in the high temperature zone is controlled at 560°C according to the performance requirements, with a residence time of 20 h and a total residence time of 42 h, to obtain the catalyst.

[0092] Example 4

[0093] The catalyst is composed of 10% active component, 75% carrier and 15% auxiliary agent by mass percentage.

[0094] The preparation method of the carrier is as follows:

[0095] S11: ZSM-5 molecular sieve and titanium dioxide were mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture A; S12: Diatomaceous earth was ground in a ball mill at a speed of 500 r / min for 0.5 h, and then dispersed in a nitric acid solution with a mass fraction of 10%, heated to 60°C, ultrasonicated for 1 h, cooled to room temperature, washed with deionized water, and dried at 80°C for 12 h to obtain diatomaceous earth powder B;

[0096] S13: Mix the mixture A and the diatomaceous earth powder B in a mass ratio of 1:2, and grind them in a ball mill at a rotation speed of 500 r / min for 0.5 h to obtain a mixture C;

[0097] S14: adding silane coupling agent KH550 to deionized water to prepare a solution with a mass fraction of 40%, heating to 60° C. to obtain solution D;

[0098] S15: putting the mixture C into the solution D, wherein the mass ratio of the mixture C to the silane coupling agent KH550 is 2:1, stirring at 60° C. at a speed of 150 r / min for 4 h, filtering, and drying at 80° C. for 12 h to obtain the carrier;

[0099] The preparation method of the active component is as follows:

[0100] S21: copper nitrate, nickel nitrate and chromium nitrate were mixed in a mass ratio of 2:1:1, 1 wt % of polyethylene glycol 2000 was added, and the mixture was ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture E;

[0101] S22: dissolving rubidium nitrate in deionized water to prepare a rubidium nitrate solution with a mass fraction of 40%, dispersing mixture E in the rubidium nitrate solution, wherein the mass ratio of mixture E to rubidium nitrate is 2:1, heating to 50°C, and stirring at a speed of 200r / min for 1h, adding 1wt% glycine to the mixed solution, continuing to stir for 0.5h, transferring to a muffle furnace preheated to 300°C and burning for 2min, then heating to 500°C and calcining for 4h at a heating rate of 5°C / min, and after calcination, cooling and grinding to obtain the active component, wherein the particle size of the ground active component is 800 mesh;

[0102] The preparation method of the auxiliary agent is as follows:

[0103] S31: dissolving sodium dodecyl sulfate in deionized water to obtain a solution with a mass fraction of 50%, and heating the solution to 60° C. to obtain a solution F;

[0104] S32: Add ammonium heptamolybdate to solution F, wherein the mass ratio of ammonium heptamolybdate to the cationic surfactant is 2:3, and ultrasonicate is performed at 60°C for 0.5h. After the ultrasonication is completed, the solution is filtered, dried at 80°C for 12h, cooled and ground after drying to obtain the auxiliary agent, wherein the particle size of the auxiliary agent obtained by grinding is 800 mesh.

[0105] A method for preparing a water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitrification catalyst. The specific process of the catalyst preparation method is as follows:

[0106] S61: Put the active component, carrier and auxiliary agent into a high-speed mixer according to the proportion, add 1wt% oxalic acid, add a certain amount of deionized water, mix and stir, the mixer speed is 3000r / min, the time is 5h, and a muddy mixture G is obtained;

[0107] S62: The muddy mixture G is extruded into a through-hole square honeycomb body by a high-pressure extruder using an integrated die, and cut into the required length; then dried by hot air, and the temperature is controlled by a computer program and kept in sections at 25°C, 28°C, 31°C, 35°C, 40°C, 45°C, 50°C, 55°C, 58°C, and 60°C for 24 hours at each of the above temperatures, wherein the humidity in the drying room is required to be maintained at more than 80% before 40°C; then calcined by a program-controlled electric heating section-by-section insulation method, with the residence time in the low temperature zone of 120°C and the medium temperature zone of 400°C being 3 hours and 13 hours respectively, and the temperature in the high temperature zone is controlled within the range of 480°C according to the performance requirements, with a residence time of 20 hours and a total residence time of 36 hours, to obtain the catalyst.

[0108] Comparative Example 1

[0109] In this comparative example, no silane coupling agent KH550 was added during the preparation of the carrier, and the remaining steps were consistent with those of Example 1.

[0110] Comparative Example 2

[0111] In this comparative example, no ZSM-5 molecular sieve is added during the preparation of the carrier, and the remaining steps are consistent with those of Example 1.

[0112] Comparative Example 3

[0113] In this comparative example, titanium dioxide was not added during the preparation of the carrier, and the remaining steps were consistent with those of Example 1.

[0114] Comparative Example 4

[0115] In this comparative example, diatomaceous earth was not added during the preparation of the carrier, and the remaining steps were consistent with those of Example 1.

[0116] Comparative Example 5

[0117] In this comparative example, rubidium nitrate was not added during the preparation of the active component, and the remaining steps were consistent with those of Example 1.

[0118] Comparative Example 6

[0119] In this comparative example, copper nitrate was not added during the preparation of the active component, and the remaining steps were consistent with those of Example 1.

[0120] Comparative Example 7

[0121] In this comparative example, nickel nitrate was not added during the preparation of the active component, and the remaining steps were consistent with those of Example 1.

[0122] Comparative Example 8

[0123] In this comparative example, chromium nitrate was not added during the preparation of the active component, and the remaining steps were consistent with those of Example 1.

[0124] Comparative Example 9

[0125] In this comparative example, no cationic surfactant is added during the preparation of the auxiliary agent, and the remaining steps are consistent with those of Example 1.

[0126] The denitration catalysts according to Examples 1 to 4 and Comparative Examples 1 to 9 of the present invention were subjected to performance testing and denitration experiments, and the results are shown in Table 1. The testing method is as follows:

[0127] (1) Denitrification efficiency determination: The simulated flue gas composition is: NO x , NH3, O2 and carrier gas N2, with an air velocity of 7500h -1 , NO x Concentration is 1200mg / m 3 , NH3 / NO x Molar ratio = 1, O2 concentration: 16%, reaction temperature controlled at 100~280℃. The gas flow is controlled by a mass flow meter. Before entering the reactor, the gas is mixed by a gas mixer and then preheated by a preheater. x The concentration is measured by a flue gas analyzer. In order to eliminate the influence of surface adsorption, the system starts collecting and testing after the ventilation operation is stable for 30 minutes.

[0128] (2) Determination of sulfur and water resistance: The simulated flue gas composition is: NO x , NH3, SO2, H2O, O2 and carrier gas N2, with an air velocity of 7500h -1 , NO x Concentration is 1200mg / m 3 , NH3 / NO x Molar ratio = 1, O2 concentration: 16%, SO2 concentration: 1200mg / m 3, H2O content: 25vol%; reaction temperature is controlled at 120℃. The flow rate of each gas is controlled by a mass flow meter. Before entering the reactor, the gas is mixed by a gas mixer and then preheated by a preheater. x The concentration is measured by a flue gas analyzer. In order to eliminate the influence of surface adsorption, the system starts collecting and testing the denitrification efficiency after the ventilation operation is stable for 30 minutes.

[0129] (3) Determination of resistance to alkali metals and alkaline earth metals: Two test pieces of each catalyst were cut and placed in 2% potassium hydroxide + 2% sodium hydroxide solution and 2% calcium hydroxide + 2% magnesium hydroxide solution respectively. After being placed at room temperature for 72 hours, the test pieces were taken out and placed in a forced air drying oven at 115°C for 3 hours, and then placed in a muffle furnace for calcination at 450°C for 3 hours. The test pieces were then taken out and the denitrification efficiency was tested respectively. The test conditions were: flue gas composition: NO x , NH3, O2 and carrier gas N2, with an air velocity of 7500h -1 , NO x The concentration is 1200mg / m 3 , NH3 / NO x Molar ratio = 1, O2 concentration: 16%, reaction temperature controlled at 120°C.

[0130] Table 1:

[0131]

[0132] As shown in Table 1, the present invention uses NO at different temperatures x It can be observed from the conversion rate that the embodiments have better denitration efficiency, and at the same temperature (120°C), it can be observed that the catalyst prepared by the embodiments of the present invention has better comprehensive performance.

[0133] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitrification catalyst, characterized in that: In terms of mass percentage, the catalyst is composed of 5-15% active component, 75-85% carrier and 5-15% auxiliary agent. Wherein, the preparation method of the carrier is as follows: S11: ZSM-5 molecular sieve and titanium dioxide were mixed in a mass ratio of 1:2, and ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture A; S12: Grind the diatomite in a ball mill at a speed of 500 r / min for 0.5 h, disperse it in a 10% by mass nitric acid solution, heat it to 60° C., ultrasonicate it for 1 h, cool it to room temperature, wash it with deionized water, and dry it at 80° C. for 12 h to obtain diatomite powder B; S13: Mix the mixture A and the diatomaceous earth powder B in a mass ratio of 1:(1-3), and grind them in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture C; S14: adding silane coupling agent KH550 to deionized water to prepare a solution with a mass fraction of 30-50%, heating to 60° C. to obtain solution D; S15: putting the mixture C into the solution D, wherein the mass ratio of the mixture C to the silane coupling agent KH550 is 2:1, stirring at 60° C. at a speed of 150 r / min for 4 h, filtering, and drying at 80° C. for 12 h to obtain the carrier; The preparation method of the active component is as follows: S21: copper nitrate, nickel nitrate and chromium nitrate were mixed in a mass ratio of 2:1:1, 1 wt % of polyethylene glycol 2000 was added, and the mixture was ground in a ball mill at a speed of 500 r / min for 0.5 h to obtain a mixture E; S22: dissolving rubidium nitrate in deionized water to prepare a rubidium nitrate solution with a mass fraction of 30-40%, dispersing mixture E in the rubidium nitrate solution, wherein the mass ratio of mixture E to rubidium nitrate is 2:1, heating to 50°C, and stirring at a speed of 200r / min for 1h, adding 1wt% glycine to the mixed solution, continuing to stir for 0.5h, transferring to a muffle furnace preheated to 250-300°C and burning for 2-3min, then heating to 500°C and roasting for 4h, the heating rate of the muffle furnace is 5°C / min, after roasting, cooling and grinding to obtain the active component, the particle size of the active component obtained by grinding is 800 mesh; The preparation method of the auxiliary agent is as follows: S31: dissolving a cationic surfactant in deionized water to obtain a solution with a mass fraction of 50%, and heating the solution to 60° C. to obtain a solution F; S32: Add ammonium heptamolybdate to solution F, wherein the mass ratio of ammonium heptamolybdate to the cationic surfactant is 2:3, perform ultrasonic treatment at 60°C for 0.5h, filter after the completion of ultrasonic treatment, dry at 80°C for 12h, cool and grind after drying to obtain the auxiliary agent.

2. The water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitration catalyst according to claim 1, characterized in that: The cationic surfactant in S31 is one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and hexadecyltrimethylammonium bromide.

3. The water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitration catalyst according to claim 1, characterized in that: The particle size of the auxiliary agent obtained by grinding in S32 is 800 mesh.

4. A method for preparing a water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitration catalyst, based on the water-resistant, sulfur-resistant, and poisoning-resistant ultra-low temperature denitration catalyst according to any one of claims 1 to 3, characterized in that: The specific process of the preparation method of the catalyst is as follows: S61: Put the active component, carrier and auxiliary agent into a high-speed mixer according to the proportion, add 1wt% oxalic acid, add a certain amount of deionized water, mix and stir, the mixer speed is 3000r / min, the time is 5h, and a muddy mixture G is obtained; S62: The muddy mixture G is extruded into a through-hole square honeycomb body through a high-pressure extruder using an integrated die, and cut into a required length; then it is dried with hot air, and kept warm for 18 to 24 hours in 10 temperature sections between 25 and 60°C, and then calcined at 120 to 560°C for 31 to 42 hours to obtain the catalyst.

5. The method for preparing a water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitration catalyst according to claim 4, characterized in that: The mixture G in S61 is a long strip of mud.

6. The method for preparing a water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitration catalyst according to claim 4, characterized in that: In the S62, hot air is used for drying, and the temperature is controlled by a computer program to be kept warm at 25°C, 28°C, 31°C, 35°C, 40°C, 45°C, 50°C, 55°C, 58°C, and 60°C for 18 to 24 hours at each temperature, wherein the humidity in the drying room is required to be maintained at more than 80% before 40°C; and then program-controlled electric heating is used for calcination in a segmented insulation manner, with the residence time in the low temperature zone of 120 to 180°C and the medium temperature zone of 300 to 400°C being not less than 3 hours and 13 hours respectively, and the temperature in the high temperature zone is controlled within the range of 480 to 560°C according to performance requirements, with the residence time being not less than 15 hours, and the total residence time being 31 to 42 hours.

7. The method for preparing a water-resistant, sulfur-resistant and poisoning-resistant ultra-low temperature denitration catalyst according to claim 4, characterized in that: The catalyst prepared in S62 is a cube honeycomb catalyst.

Citation Information

Patent Citations

  • Nitric acid exhaust gas denitration catalyst and preparation method thereof

    CN102631921A

  • Preparation method of low-cost honeycomb denitration catalyst

    CN103191718A